Role of Corporate Social Responsibility in Croatian Export Companies (ENTRENOVA - ENTerprise REsearch InNOVAtion Journal, 2018)
Continuous globalization, rapid development of information-communication technologies, and the presence of new burning challenges for the global community have contributed to the perception of corporate social responsibility as a strategic tool that allows for successful differentiation and sustainable competitive advantage. The goal of this paper is to offer a short overview of the role of a strategic approach to corporate social responsibility, as well as emphasize the importance of such an approach in creating competitive advantage for a company, but also of sustainability of society as a whole. The paper is based on a primary research questionnaire conducted on middle-sized and large Croatian export companies, as well as a systematic analysis of previously published relevant international scientific papers in the area of corporate social responsibility.This work is licensed under a Creative Commons Attribution-NonCommercial 4.0 International License.